Biotecnologia e desenvolvimento: o papel da propriedade intelectual - Zanini, Luciana Olivares (2011)
The difficulties in adopting a culture of intellectual property within the academic and technology sectors limit the development of the country. The low initiative in actively using the available legal resources to transform knowledge in to investment, with a view to achieving common gains, constitutes an important issue. One of the solutions to overcome such difficulties is to establish a culture of intellectual property. The combination of objectives and efforts to establish such a culture is a relevant strategy, in view of the great complexity involved in product and process innovation; in the context of concentration of productive assets, in the new information era, and in the internationalization of economies. A local culture of intellectual property allows for a profound change in the pattern of the relationship between the State and society, increasing participation, negotiation and democratization. The aim of this study was to evaluate whether the development policies and the related legislation achieve their objectives, among which the technological development rooted in the registration of biotechnology patents. To that end, a study was carried out on the perception of students and professors from the Graduate Program in Biotechnology of the Federal University of Pelotas, seeking to identify the level of knowledge of biotechnology researchers regarding the protection of intellectual property. This study revealed that researchers are receptive to intellectual property and that providing more information on the topic may contribute to new and efficient strategies to develop research capacity and the university. The results of this study can be of great value to guide actions towards a culture of biotechnology intellectual property within the university.